Role of Antibiotic-Impregnated Shunts in Preventing Shunt-Related Infections: Long-Term Outcomes - Muhammad Tahir, Madiha Amjad, Rashid Ali Khosa, Ashan Ali, Muhammad Inam, Abrar Haider (Pakistan Journal of Medical & Health Sciences, 2024)
Background: The most common treatment for hydrocephalus is the implantation of a ventriculoperitoneal (VP) shunt. Shunt-related infections, however, continue to be a serious problem that raises morbidity, mortality, lengthens hospital stays, and increases healthcare expenses. By preventing bacterial colonisation, antibiotic-impregnated shunts (AIS) have been developed to lower infection rates. Objective: The purpose of this study is to compare the long-term clinical results of antibiotic-impregnated shunts with those of conventional shunts and to determine how well they prevent infections connected to shunts. Methodology: Patients receiving VP shunt implantation for hydrocephalus were the subjects of a retrospective comparison research. Patients were split into two groups: those who received conventional shunts and those who received shunts impregnated with antibiotics. We gathered and examined information on demographics, shunt placement indications, postoperative infections, shunt revisions, and long-term results. Results: When compared to the conventional shunt group, the antibiotic-impregnated shunt group had a considerably lower incidence of shunt-related infections. Additionally, patients with AIS showed extended infection-free survival and reduced shunt revision rates. Conclusion: individuals with hydrocephalus benefit from antibiotic-impregnated shunts since they lower the risk of shunt-related infections and enhance long-term results. Regular usage of these may improve patient prognosis and lessen the burden of healthcare. Keywords: neurosurgery, long-term results, antibiotic-impregnated shunt, hydrocephalus, ventriculoperitoneal shunt, and shunt infection.